2021
DOI: 10.29271/jcpsp.2021.06.703
|View full text |Cite
|
Sign up to set email alerts
|

Flap Monitoring using Thermal Imaging Camera: A Contactless Method

Abstract: Objective: To determine the accuracy of the thermal imaging camera for the detection of vascular insult before the onset of permanent tissue damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Unit and disposable costs appear to limit the use of this efficient monitoring method 5,10 . Thermal scan 12 and Macrophage Migration Inhibitory Factor 13 are still under evaluation. LDF is a non-invasive method enabling the monitoring of microvascular blood flow 14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unit and disposable costs appear to limit the use of this efficient monitoring method 5,10 . Thermal scan 12 and Macrophage Migration Inhibitory Factor 13 are still under evaluation. LDF is a non-invasive method enabling the monitoring of microvascular blood flow 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Properties of the ideal free flap monitoring technique should be: inexpensive; harmless to both patient and flap; produce rapid, reliable, and objective results; simple to interpret by relatively inexperienced personnel; and applicable to all types of free flaps 6 . Various methods have been proposed, including prick test 7 , microdialysis 8 , Doppler (both implantable and external) 9 , Near-Infrared Spectroscopy (NIRS) 10 , Single Photon Emission Computed Tomography (SPECT) 11 , thermal scan 12 , Macrophage Migration Inhibitory Factor 13 and Laser-Doppler Flowmetry (LDF) 14,15 . The latter exploits wavelength variations of photons hitting blood red cells (BRC) while flowing.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in free flaps performed in breast reconstruction surgeries, surgeons have been using IRT, together with Doppler ultrasound and computed tomography angiography techniques, to monitor the viability of the flap but also as a novel tool to preoperatively locate perforator vessels in flaps [ 23 ]. In contrast, some studies reported that IRT was unable to detect a case of poorly perfused flap until the skin transplant was dead; nonetheless, the accuracy of the technique was estimated at 96.43% [ 77 ].…”
Section: Thermal Imaging Applied To Assess Tissular Damage Degree And...mentioning
confidence: 99%
“…Thermal cameras have proven their value in medicine and are nowadays readily available at a low cost. Their non-invasive nature and ability to provide immediate, quantitative data make infrared thermal imaging an attractive adjunct in flap monitoring [5]. Various clinical applications 2 involving depth analysis of burns, detection of complications for diabetic foot ulcer and preoperative planning of perforators using infrared thermal imaging have been made in plastic surgery [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Various clinical applications 2 involving depth analysis of burns, detection of complications for diabetic foot ulcer and preoperative planning of perforators using infrared thermal imaging have been made in plastic surgery [6,7]. Furthermore, there have been several publications describing flap monitoring using infrared thermal imaging [5].…”
Section: Introductionmentioning
confidence: 99%